The Role and Effect of the Comprehensive Music Therapy in Project Sleep: A Multi-Disciplinary Quality Improvement Project. - W Chang-Lit; J Loewy; J Fox; E Grabscheid; J Fogel (Journal of Sleep And Sleep Disorder Research, 2018)
Sleep is vital for the maintenance of physical health and mental wellbeing. Sleep also plays a cardinal role in the process of healing. It is estimated that 50 to 70 million Americans suffer chronically from sleep disturbances and insufficiency, which not only hinders daily functioning but also adversely affects health, quality of life and longevity.1 Deficient sleep is associated with an increased risk of developing chronic diseases such as hypertension, diabetes, obesity, heart disease, stroke, depression, frequent mental distress, as well as increased mortality, and reduced quality of life and productivity.1,2Aging, medical conditions, pain, and mental illness further aggravate sleep disturbances such as insomnia, sleep fragmentation and daytime sleepiness.3, 4, 5, 6, 7, 8 The a common treatment for sleep disturbances and insomnia is pharmacological therapy. Benzodiazepines may have negative long-term side effects including residual daytime sedation and tolerance development. Withdrawal difficulties may increase dependency. In the older patient there are safety issues related to daytime sedation including increase risk of falls. With the importance of sleep in hospital recovery and the side effects of sleep medication becoming more widely recognized, there has been an impetus to s use nonpharmacological alternatives , such as music.. This pilot study builds on the potential impact of music’s effectivity by introducing music therapy as a safe, cost effective and culturally sensitive intervention.
Keywords: Music Therapy